Hypervelocity impact testing of materials for additive construction: Applications on Earth, the Moon, and Mars. (2017) - Ordonez, Erick; Edmunson, Jennifer; Fiske, Michael; Christiansen, Eric; Miller, Joshua; Davis, Bruce (Alan); Read, Jon; Johnston, Mallory; Fikes, John
Abstract: The National Aeronautics and Space Administration's Additive Construction with Mobile Emplacement project is investigating the building of infrastructure elements on planetary surfaces by 3-dimensional printing with construction materials made of in-situ resources. Likewise, the United States Army Corps of Engineers' Additive Construction of Expeditionary Structures project seeks to 3-dimensionally print structures made of concrete available everywhere on Earth. These construction materials must resist failure due to micrometeorite impact and ballistic impact, respectively. Samples were tested for resistance to hypervelocity impact with a 2.0mm aluminum sphere at a velocity of 7.00±0.2km/s. Ordinary Portland Cement-bearing samples were not perforated and did not spall, including the sample that was additively constructed. This indicates printed construction material can withstand impact. The Sorel cement sample was not perforated, but fractured and spalled. Thus, Sorel cement in its current formulation would not be considered a feasible construction material for planetary structures.